(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2022)
Efficient teaching approaches are critical to promote a positive attitude among learners of History at secondary schools. Learners’ behaviour during History lessons and attitude towards the subject can be affected by a number of factors, including teaching methods, teaching styles, teacher’s commitment and work ethic, etc. The study was conducted to examine the effect of using images in relation to the behaviour and attitude of learners towards the subject History. The study applies analytical research involving learners from a convenient group of schools around Mankweng in the use of the People, Space and Time (PST) image analysis strategy as a teaching strategy to affect the behaviour of learners towards the subject History. It uses image analysis to determine the effect of PST on the voluntary participation of learners in the History classroom. The results show that with careful organisation of visuals and crafting of questions, the PST method had a significant positive effect on learners’ behaviour and attitude towards the subject. It was also observed that an increased number of learners responded comfortably to PST during class discussions. Teacher mentors have also shown interest in this strategy as learners seemed lively in class, with disinterest turning into interest as learner participation increased. The study concluded that an expert analysis of images is a key resource in the teaching of History.